What is the likelihood that underage youth can obtain marijuana from licensed recreational marijuana outlets in California, a state where recreational marijuana is legal?. (September 2022) - Fell, James C.; Toomey, Traci; Eichelberger, Angela H.; Kubelka, Julie; Schriemer, Daniel; Erickson, Darin
Highlights: Any level of marijuana can impair driving. The access to recreational marijuana by underage patrons at outlets was assessed. Pseudo-underage patrons were required to show age ID in each outlet visited. Further research is needed on where underage youth obtain their marijuana. Abstract: Objective: Since 2012, 19 states and the District of Columbia have legalized the recreational use of marijuana for adults ages 21 and older. Marijuana use at any level can impair driving performance. Prior research on enforcement of the minimum legal marijuana use age of 21 (MLMU-21) laws is limited. The objective of the current study was to assess the ease of access to marijuana by underage patrons at recreational marijuana outlets in California, where recreational marijuana was legalized in 2016. Method: Pseudo-underage patrons were sent to 50 randomly selected licensed recreational marijuana outlets in the state to see if they could enter the outlet without showing a valid identification of their age. Results: Pseudo-underage patrons were required to show age identification to enter in 100% of the licensed recreational marijuana outlets visited. Conclusions: It appears that licensed California recreational marijuana outlets avoid selling marijuana to underage customers. One reason could be a strong incentive for recreational marijuana outlet owners and managers to avoid being shut down for an illegal activity. Practical Application: Underage youth are not obtaining marijuana at licensed recreational outlets. Future studies and cannabis enforcement agencies should investigate whether underage patrons attempt to use fake IDs at licensed marijuana outlets and whether youth are obtaining marijuana from illicit dispensaries or from social sources.